Synthesis, chemical and physical properties of lanthanide(III) (Nd, Gd, Tb) complexes derived from (E)-ethyl 4-(2-hydroxybenzylideneamino)benzoate. (1st August 2022) - Abu-Yamin, Abdel-Aziz; Taher, Deeb; Korb, Marcus; Al Khalyfeh, Khaled; Ishtaiwi, Zakariyya; Juwhari, Hassan K.; Helal, Wissam; Amarne, Hazem; Mahmood, Sami; Loloee, Reza; YouSef, Yaser A.; Ghazzy, Asma; et al.
Graphical abstract: A straightforward synthetic methodology for the preparation of lanthanide(III) complexes is described. The molecular solid state structures, intermolecular forces, UV-excitation emissions, DFT calculations and susceptibility measurements of the investigated compounds are reported. Abstract: The 1:2 reaction between Ln(NO3 )3 ·6H2 O (1 ) (Ln = Nd (a ), Gd (b ) or Tb (c )) and (( E )-ethyl 4-((2-hydroxybenzylidene)amino)benzoate) (L N, OH ) in ethanol has provided access to the complexes [Ln III (L NH, O )2 (NO3 )3 (H2 O)] (2a–c ) in good yield. The isomorphous structures of 2a–c have been determined by single-crystal X-ray crystallography. The Ln III ions in 2a–c are coordinated by 9 oxygen atoms: two from the phenolate oxygen atoms of the Schiff bases, six from three chelating nitrato groups and one aqua ligand. The ligands L N, OH behave as monodentate phenolate O– donors, whereby an additional hydrogen atom is bonded to the imino nitrogen atom, resulting in a formally neutral ligand that adopts an exceptionally unusual coordination mode engaging in the zwitterionic form. The nine donor atoms that define the coordination polyhedra surrounding the Ln III ion are best described as capped square antiprisms. The crystal structures are based on a variety of intermolecular interactions. Hirshfeld surface analysis was used to assess the degree of interactions between the molecules. Susceptibility measurements on 2a –2c confirm the occurrence of the free ion ground 2 S +1 LJ state at room temperature. However, the magnetization measurements at 2 K revealed a lack of saturation at the highest applied field of 70, 000 Oe for both 2a and 2c, indicating the presence of substantial magnetic anisotropy in these compounds. On the other hand, 2b exhibits perfect paramagnetic behavior with magnetic saturation at high fields, indicating the absence of significant magnetic anisotropy in this compound. Solid-state IR and UV/VIS data are discussed in terms of the structural features. Solid 2a–c emit in the visible region upon UV-Excitation with the emission exhibiting dopant characteristics.